Kontribusi Pemikiran KH. Hasyim Muzadi Terhadap Islam Indonesia - Anwar Sa’dullah; Imam Muslimin; Triyo Supriyatno (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2020)
Abstract This article discusses about KH. A. Hasyim Muzadi idea is Islam rahmatan lil 'alamin which can be used as moderate Islam or Indonesian Islam in the present context as a medium in connecting Eastern and Western thought. More details about his thoughts are described through this scientific paper. The research method used is literature study with written references containing the above themes. Technique data through observation and documentation and data analysis using integrative data analysis, namely: referring to data, display data, data reduction and data retrieval. Keywords: contribution, political KH. A. Hasyim Muzadi, Indonesian Islam